Sperm viability and acrosome integrity in national frozen bull semen - Cabrera V., Próspero (2012)
The deterioration of the sperm membrane and acrosome integrity as a method for predicting fertility in bulls was evaluated. Four bulls (2 Holstein and 2 Brown Swiss) from the National Bank of Semen, Lima-Peru were used. Acrosome integrity, sperm membrane integrity, motility, live sperm cells, volume, and sperm concentration during cooling, freezing and thawing was evaluated in 10 ejaculates per sire. In fresh semen, volume was 4.33 ml; sperm concentration was 922.5 x 106/ml and 78.5% of live cells. The individual progressive motility in diluted semen was 82.7 to 86.0% with significant difference between bulls (p<0.05). Acrosome integrity in chilled semen varied from 59.3 to 69.2% and without statistical difference between bulls. Percentage of sperm with intact acrosome decreased from 65.2 in chilled semen to 48.6% in frozen/thawed semen, without statistical difference between bulls. None significant correlation was found between motility and sperm membrane integrity or acrosome integrity.